2007
DOI: 10.1103/physrevlett.99.162502
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Blocking Measurements of the Time Delay of Fission Induced byS32,Ti48, andet al.

Abstract: The time delay in fission induced by bombardment of W with 180 MeV 32S, 240-255 MeV 48Ti, and 315-375 MeV 58Ni has been measured by observation of crystal blocking. There is a clear narrowing and a small increase in the minimum yield of the angular dips for fission compared with scaled dips for elastically scattered ions. This is interpreted as a fission delay of about 2 as, only weakly dependent on energy and atomic number. The delay is longer by 1 to 2 orders of magnitude than obtained from standard interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…However, it was too time consuming to record mask spectra with fission fragments and instead the calibration for the simultaneously recorded elastic scattering was applied as in earlier work [24,25]. We found in the present analysis that one then must correct for the different depth profiles of energy deposition in the counter.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, it was too time consuming to record mask spectra with fission fragments and instead the calibration for the simultaneously recorded elastic scattering was applied as in earlier work [24,25]. We found in the present analysis that one then must correct for the different depth profiles of energy deposition in the counter.…”
Section: Discussionmentioning
confidence: 91%
“…In our previous work [24], we observed that the y signal depends on the mass of the detected particle, and we scaled the y-coordinate for the fissions so that the axis of the fission and elastic blocking patterns occurred at the same y-coordinate. In the first analysis of the present data [25], we refined this correction and introduced a linear dependence of this y-scaling on the parameter E rest , ensuring that the coordinates of the center of the blocking dip were the same for all fission fragments as those for the elastics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However direct measurements by X-ray and crystal blocking techniques have shown very long fission delay times (∼10 -18 sec) even for the highly excited uranium-like and trans-uranium nuclei [16][17][18]. These results have not so far been explained by the viscosity effect.…”
Section: Classical Fission Delay Due To Nuclear Viscositymentioning
confidence: 99%
“…These times have to be compared with fusion-fission times which can be longer than 10 −16 s [9]. This shows that the two mechanisms are of very different nature.…”
Section: Introductionmentioning
confidence: 99%